2015
DOI: 10.1177/0003319715584725
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Decreases Mean Platelet Volume in Patients With Diabetes Mellitus

Abstract: Statins have multiple effects (also known as pleiotropic effects) on inflammation, plaque stabilization, endothelial function, and hemostasis. We evaluated the effects of rosuvastatin on mean platelet volume (MPV)--a marker for platelet activity--in patients with diabetes mellitus (DM) on rosuvastatin medication. Patients (n = 178) who were to be prescribed high-intensity rosuvastatin were retrospectively enrolled according to their medical records. Baseline and 6-month biochemical tests, automated blood count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…16,17 Hypoglycemic or hypolipidemic decreases the MPV as well as plasma glucose level 18 or cholesterol levels. 19 Hundreds of participants of this study are taking hypoglycemic agent or hypolipidemic agent, may decrease the association between MPV and hypertension incidence, because individuals with diabetes or dyslipidemia have higher hypertension incidence even on treat. Changes in MPV are chronic rather than abrupt, which is another indication that it correlates with chronic diseases such as hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…16,17 Hypoglycemic or hypolipidemic decreases the MPV as well as plasma glucose level 18 or cholesterol levels. 19 Hundreds of participants of this study are taking hypoglycemic agent or hypolipidemic agent, may decrease the association between MPV and hypertension incidence, because individuals with diabetes or dyslipidemia have higher hypertension incidence even on treat. Changes in MPV are chronic rather than abrupt, which is another indication that it correlates with chronic diseases such as hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…22 Yet other studies showed an effect of statins on the MPV. [23][24][25] The MPV levels, total numbers of white blood cells, platelets, and lymphocytes were determined by the Coulter LH Series (Beckman Coulter, Inc., Hialeah, Florida). Because MPV expands with time in EDTA, complete blood count studies were done as soon as possible (within 30 minutes) after the blood samples were drawn to minimize changes in platelet size.…”
Section: Blood Samplesmentioning
confidence: 99%
“…With rosuvastatin this action is not mediated by the improved serum lipids, 28 whereas atorvastatin achieved a significant MPV reduction in patients with the strongest concomitant lipid changes. 25 This emerging difference needs to be revisited.…”
mentioning
confidence: 91%
“…25 Conversely, pravastatin treatment did not lower the MPV. 27 More recently, the study of Akyüz et al 28 examined 178 patients with DM receiving high-dose rosuvastatin (40 mg/d) for dyslipidemia. After 6 months of treatment, there was a significant (P < .001) decrease in MPV.…”
mentioning
confidence: 99%